PENGEMBANGAN MEDIA KLIPING DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS XI SMA/MA - Rikandari Kurniawati; Agus Hermawan; Lailiyatus Sa’diyah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Procedure text is an instruction that contains steps or procedures to do something in order to achieve the goal. The results of observations in class XI IPA MA Sirojut Tholibin, researchers found that there were still many students who had difficulty in writing procedural texts based on linguistic structures and rules. The difficulty lies in the stage of finding ideas in assembling vocabulary into a systematic coherent sentence. One way that can be done to facilitate students in these problems is the use of appropriate learning media. The learning media needed for this problem are media that are able to stimulate students in developing procedural texts. For this reason, researchers conducted research and development of learning media in writing procedure texts in the form of clippings. The purpose of this research and development is to develop clipping media products and test the feasibility of clipping media products. The model used in this research and development is 4D from Sivasailam Thiagaranja, Dorothy S. Semmel, and Melvyn I. Semmel (1974) which consists of 4 stages which include Define, Design, Develop, and Dissiminate. Data collection techniques in this study were interviews with teachers, observations, and questionnaires. Questionnaires were distributed to material experts, media experts, practitioners/teachers, and students. The results of the assessment of the feasibility of learning media products by material experts get a total percentage of 95.8%, media experts get a total percentage of 96.25%, expert practitioners / Indonesian language teachers get a total percentage of 90.4%, and students get a total percentage of 85 ,7%. From the overall results of the respondent's assessment, it can be concluded that the clipping media product has very feasible criteria to be implemented in learning.